Pengaruh Corporate Governance Dalam Hubungan Firm Size Dan Leverage Terhadap Earnings Management - Farah Dzakiyyah Maulida; Erma Setiawati (Jurnal Akuntansi dan Pajak, 2024)
Earnings management is a method used by management in managing the company's financial reports through selecting accounting policies with the aim of increasing net profit and the expected company value. This research aims to analyze the influence of corporate governance in the relationship between firm size and leverage on earnings management in food and beverage companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sampling technique in this research used purposive sampling. The analytical method in this research uses multiple linear regression analysis and the number of companies that meet the criteria is 130 companies. The results of this research prove that the audit committee effects on the relationship between leverage and earnings management. Meanwhile, firm size and leverage do not effect on earnings management, and the audit committee do not effect on the relationship between firm size and earnings management.